Column structure strengthening with FRP (Fiber Reinforced Polymer) due to story addition - I Wayan Maesa Andreasnata; I Nengah Sinarta; Ni Komang Armaeni; I. P. Ellsa Sarassantika; Dang Thanh Trung; Cintantya Budi Casita; Roro Sulaksitaningrum; Sudarno P. Tampubolon (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2022)
This study focuses on strengthening scheme of an existing structure with added story. The addition of a new story increases gravitational loading, which affects the seismic and wind responses of the structure and, as a consequence, the loading combination. To ensure the structure’s capacity requirement, the strengthening scheme uses CFRP (Carbon Fiber Reinforced Polymer). In order to adequately define the structure's performance, a series of structural analyses were performed. The structure's state before and after story addition, subsequently the state after CFRP strengthening, were evaluated. It is demonstrated that the additional story to the structure causes an exceedance in internal forces; however, the strengthening with CFRP is sufficient to withstand these forces, proving that the strengthening scheme is effective and beneficial.